Multicomponent Polymers : Principles, Structures and Properties - Guojian, Wang; Junjie, Yuan (De Gruyter STEM, 2020)
The book introduces fundamental principles, phase structure, mechanism, mechanical properties, and different types of multicomponent polymers. Rheological properties, graft copolymers, block copolymers and interpenetrating polymer networks are discussed in detail as well. With abundant illustrations, it is an essential reference for polymer chemists, material scientists and graduate students.